The Willingness of Community Psychiatric Management Physicians to Preferentially Recommend Long-Acting Injections in Beijing - Jin, Lefan; Chen, Yun; Zhu, Junli; Huang, Qingzhi; Li, Bin; Xu, Ying; Xi, Rui; Lu, Wei (Frontiers in Public Health, 2021)
Background: Severe mental disorders (SMD) impose a heavy burden on individuals, society, and the country. Under the background of deinstitutionalization, more and more patients return to the community, and the community psychiatric management physicians (CPMP) play an essential role in this process. Long-acting injection (LAI) is an important way to improve compliance and reduce re-hospitalization. Some districts in Beijing have implemented the policy of free LAI. This article aims to find out the willingness of CPMP to preferentially recommend LAI and provide suggestions for follow-up promotion. Methods: All CPMP in 16 districts of Beijing were surveyed. A self-made electronic questionnaire was used to investigate the willingness to recommend LAI in priority. Descriptive statistics, Chi-square test, and logistic regression were used to analyze the data. Results: The willingness of CPMP to preferentially recommend LAI is up to 80%. Participants aged 40-49, female, with higher self-evaluation of psychiatric management knowledge, managing patients who have used LAI in the past, and working in communities with the free LAI policy have higher willingness to recommend LAI in priority. Conclusion: CPMP in Beijing have a positive attitude towards LAI, and most of them have the willingness to recommend LAI to the patients in priority. The recommendation willingness is the basis of prescription decision-making. Therefore, the coverage of free LAI policy should be further expanded in the future to improve the recommendation willingness and thus improve the injection rate of LAI.